Alkali-activated cementing material and preparation method thereof

By using industrial waste and liquid sodium silicate and other raw materials to prepare alkali-excited gelling materials, the problems of energy consumption and pollution of traditional silicate cement are solved, and high-strength, durability and environmentally friendly building materials are achieved.

CN119551961APending Publication Date: 2025-03-04SHANDONG LUQIAO GROUP CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311129633.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Traditional silicate cement has high energy consumption, high pollution and negative impact on the environment during production and use, and it is difficult to meet the high strength and durability requirements of bridge construction for building materials.

Method used

A alkali-excited gelling material was developed. By using industrial waste such as slag, garbage ash, fly ash, etc., and adding liquid sodium silicate and NaOH as excitants, a gelling material with excellent mechanical properties and high durability was prepared.

Benefits of technology

This alkali-excited gelling material not only has mechanical strength comparable to or even better than silicate cement concrete, but also shortens construction time, reduces resource consumption and environmental hazards, and is suitable for large-scale promotion and application in building structures.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of cementing materials for rigid pavement, and relates to an alkali-activated cementing material and a preparation method thereof, and the alkali-activated cementing material comprises the following main components: 160-200 parts of slag, 140-170 parts of garbage ash, 220-260 parts of fly ash, 100-140 parts of sodium silicate, 16-24 parts of NaOH, 140-160 parts of water and 1200-1260 parts of sand. The water-binder ratio of the alkali-activated cementing material is 0.28 to 0.38. The alkali-activated cementing material prepared by the technical scheme of the invention has the characteristics of simple preparation, high early strength, high later strength, fast setting and hardening, good fire resistance, good environmental protection performance and the like, can significantly improve the working performance and durability of a building structure, can realize large-scale recycling of industrial wastes, and has wide application prospects. And environmental pollution caused by engineering construction is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cementitious materials for rigid paving, and mainly relates to an alkali-activated cementitious material and a preparation method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] As countries pay more attention to traditional building materials, silicate cement has attracted more and more attention due to its high energy consumption, high pollution and great impact on the environment during production and use. And with the continuous advancement of bridge construction, the demand for cement has further increased, and there is an urgent need to produce an energy-saving, environmentally friendly, low-carbon and green building material to replace traditional silicate cement.

[0004] As an important component of building structure, the mechanical properties and durability of the material itself directly affect the service life of the entire structure.

[0005] For the testing indicators of cementitious materials, the commonly used mechanical properties are compressive strength, flexural strength, elastic modulus, and the working performance mainly includes fluidity and initial setting time. The above indicators are mainly important factors to judge whether the material can be carried out normally and the safety performance of the reaction. Summary of the invention

[0006] The purpose of the present invention is to provide an alkali-activated cementitious material and a preparation method thereof. The alkali-activated cementitious material has mechanical strength equivalent to or even better than that of silicate cement concrete, can shorten the construction time, has more obvious early strength and high strength performance, and also has more obvious advantages in durability. Moreover, the cementitious material is made of industrial waste, and its preparation process does not require the consumption of a large amount of non-renewable resources, which can reduce resource consumption and reduce harm to the environment. It is suitable for large-scale promotion and application in building structures.

[0007] In view of the current research on building materials at home and abroad, the present invention has developed an alkali-activated cementitious material which can shorten the construction time, meet the engineering quality standards and is environmentally friendly.

[0008] In order to achieve the above technical objectives, the present invention adopts the following technical solutions: The first aspect of the present invention provides an alkali-activated gel material: The invention is composed of the following raw materials in parts by weight: 160-200 parts of slag, 140-170 parts of garbage ash, 220-260 parts of fly ash, 100-140 parts of liquid sodium silicate, 16-24 parts of NaOH, 140-160 parts of water and 1200-1260 parts of sand; the water-to-binder ratio of the alkali-activated cementitious material is 0.28-0.38.

[0009] Furthermore, the average particle size of the sand is 0.08 to 2.0 mm.

[0010] Preferably, the alkali-activated cementitious material is composed of the following raw materials in parts by weight: 170-190 parts of slag, 150-160 parts of garbage ash, 230-250 parts of fly ash, 110-130 parts of liquid sodium silicate, 18-22 parts of NaOH, 145-155 parts of water, and 1220-1240 parts of sand, and the water-to-cement ratio of the alkali-activated cementitious material is 0.30-0.36.

[0011] More preferably, the alkali-activated cementitious material is composed of the following raw materials in parts by weight: 180 parts of slag, 155 parts of garbage ash, 240 parts of fly ash, 125 parts of liquid sodium silicate, 20 parts of NaOH, 150 parts of water, and 1220-1240 parts of sand, and the water-to-cement ratio of the alkali-activated cementitious material is 0.34.

[0012] Furthermore, the slag density is 2.88 g / cm 3 , the density of garbage ash is 2.53g / cm 3 The density of fly ash is 1.81g / cm 3 .

[0013] The second aspect of the present invention provides a method for preparing an alkali-activated gelling material, comprising the following steps: (1) Dissolve NaOH in water to dissolve it; (2) uniformly mixing slag, garbage ash and fly ash to obtain a first mixture; (3) adding the NaOH solution prepared in step (1) into the first mixed material prepared in step (2), mixing them evenly, to obtain a second mixed material; (4) adding liquid sodium silicate into the second mixed material prepared in step (3), mixing them evenly, to obtain a third mixed material; (5) Adding sand into the third mixed material prepared in step (4), mixing them evenly, and obtaining the alkali-activated cementitious material.

[0014] The third aspect of the present invention provides the use of the above-mentioned alkali-activated cementitious material in bridge construction.

[0015] Due to the fast early coagulation and hardening characteristics of alkali-activated cementitious materials, the alkali-activated cementitious materials should be quickly poured onto the steel bridge deck, compacted by vibration using engineering equipment, smoothed on the surface and steam-cured for 28 days using a bridge steam engine.

[0016] The biggest advantage of alkali-activated cementitious materials is that they use industrial waste as the main raw material, which not only reduces the demand for cement, but also has the advantage of large-scale recycling of industrial waste, which is highly consistent with my country's environmental protection concept.

[0017] In the present invention, since the alkali-activated cementitious material shrinks greatly at an early age, adding sand can reduce its shrinkage performance, reduce concrete cracking caused by drying or temperature changes, and improve the durability of the project. Sand can also improve the fluidity of the alkali-activated cementitious material, making it easier to construct and pour, improve the work efficiency of workers, and reduce construction costs.

[0018] The admixtures described in the present invention are slag, garbage ash and fly ash. Such admixtures can reduce the porosity inside the alkali-activated concrete, reduce water penetration and erosion by harmful substances such as carbon dioxide and sulfate, and improve the durability of the concrete, such as antifreeze, anti-seepage and anti-corrosion. Fine powders such as slag, garbage ash and fly ash are active, and their high early activity can promote the early strength development and hardening speed of concrete. At the same time, fine powders such as slag, garbage ash and fly ash are cheaper than cement, and can replace the use of cement to reduce engineering costs.

[0019] The present invention adds sodium silicate as an activator in the mix design. Because the alkali-activated cementitious material has the characteristic of high shrinkage at an early age, in order to reduce the risk of cracking, sodium silicate is added to achieve the purpose of reducing the shrinkage rate of the alkali-activated material, and the engineering quality is higher.

[0020] The liquid sodium silicate of the present invention can be used as an activator to establish a highly alkaline activating environment, thereby activating the polymerization reaction performance of the raw materials. At the same time, the shrinkage rate of concrete can be reduced, thereby achieving the hardening and strength improvement of concrete. Sodium silicate can also reduce the water absorption of concrete, improve the durability of concrete, resist chloride corrosion, sulfate corrosion, etc., thereby extending the service life of concrete.

[0021] The beneficial effects of the present invention are: (1) The fluidity of an alkali-activated cementitious material involved in the technical solution of the present invention is about 176 mm, showing excellent fluidity and reducing the construction difficulty of steel bridge deck concrete paving materials.

[0022] (2) The technical solution of the present invention involves an alkali-activated cementitious material, which has a 28-day compressive strength of 71 MPa, a flexural strength of 14 MPa, and an elastic modulus of 30 Gpa. Its performance is far superior to that of ordinary Portland cement, and it has good mechanical properties and can greatly improve the safety performance of the structure.

[0023] (3) The technical solution of the present invention involves an alkali-activated cementitious material, which uses industrial waste materials such as slag, garbage ash and fly ash to reduce the use of cement, thereby saving energy and protecting the environment.

[0024] (4) The present invention does not use cement in the mix design, and uses slag, garbage ash, fly ash and other industrial waste residues to replace cement, so that the industrial waste residues can be reused and energy can be saved.

[0025] (5) The present invention adds sodium silicate as an activator in the mix design. Because alkali-activated cementitious materials have the characteristic of high shrinkage at an early age, in order to reduce the risk of cracking, sodium silicate is added to achieve the purpose of reducing the shrinkage rate of alkali-activated materials, and the engineering quality is higher. DETAILED DESCRIPTION

[0026] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0027] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0028] The following examples all adopt the following steps to prepare the alkali-activated gelling material: (1) Dissolve NaOH in water to dissolve it; (2) uniformly mixing slag, garbage ash and fly ash to obtain a first mixture; (3) adding the NaOH solution prepared in step (1) into the first mixed material prepared in step (2), mixing them evenly, to obtain a second mixed material; (4) adding liquid sodium silicate into the second mixed material prepared in step (3), mixing them evenly, to obtain a third mixed material; (5) Adding sand into the third mixed material prepared in step (4), mixing them evenly, and obtaining the alkali-activated cementitious material. Example 1

[0029] An alkali-activated gelling material comprises the following raw materials in parts by weight: 1230 parts of sand with an average particle size of 0.08-2.0 mm, 180 parts of slag, 155 parts of garbage ash, 240 parts of fly ash, 120 parts of liquid sodium silicate with a modulus of 2.8, 20 parts of NaOH, and 150 parts of water. The water-to-binder ratio of the alkali-activated cementitious material is 0.34. Example 2

[0030] An alkali-activated gelling material comprises the following raw materials in parts by weight: 1200 parts of sand with an average particle size of 0.08-2.0 mm, 200 parts of slag, 140 parts of garbage ash, 260 parts of fly ash, 100 parts of liquid sodium silicate with a modulus of 2.8, 24 parts of NaOH, and 140 parts of water; the water-to-cement ratio of the alkali-activated cementitious material is 0.28. Example 3

[0031] An alkali-activated gel material comprises the following raw materials in parts by weight: 1260 parts of sand with an average particle size of 0.08-2.0 mm, 160 parts of slag, 170 parts of garbage ash, 220 parts of fly ash, 140 parts of liquid sodium silicate with a modulus of 2.8, 16 parts of NaOH, and 160 parts of water; the water-to-cement ratio of the alkali-activated cementitious material is 0.38.

[0032] The standard specimens of the alkali-activated cementitious materials described in Examples 1-3 were subjected to performance tests according to the following test methods and standards after standard curing for 28 days. The performance data obtained are shown in Table 1: (1) Compressive strength: The compressive strength of concrete was tested according to the Standard for Test Methods of Mechanical Properties of Ordinary Concrete GB / T50081-2002. The specimen size was a cube of 150 mm × 150 mm × 150 mm. (2) Flexural strength: The concrete expansion strength was tested according to the Standard for Test Methods of Mechanical Properties of Ordinary Concrete GB / T50081-2002. The specimen size was a small beam specimen of 150 mm × 150 mm × 550 mm. (3) Elastic modulus: The elastic modulus of concrete was tested according to the Standard for Test Methods of Mechanical Properties of Ordinary Concrete (GB / T50081-2002). The specimen size was a prism of 150 mm × 150 mm × 300 mm.

[0033] Table 1 Alkali-activated gelling material test data project Compressive strength (MPa) Flexural strength (MPa) Elastic modulus (GPa) Example 1 71 14 31 Example 2 69 13 28 Example 3 70 13 30 From Table 1, it can be seen that the compressive strength of the embodiment of the present invention can reach 71 MPa, the flexural strength can reach 14 MPa, and the elastic modulus can reach 31 Gpa, indicating that it has good mechanical properties.

[0034] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of them with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An alkali-activated gelling material, characterized in that: The invention is composed of the following raw materials in parts by weight: 160-200 parts of slag, 140-170 parts of garbage ash, 220-260 parts of fly ash, 100-140 parts of sodium silicate, 16-24 parts of NaOH, 140-160 parts of water and 1200-1260 parts of sand; the water-to-binder ratio of the alkali-activated cementitious material is 0.28-0.

38.

2. The alkali-activated gelling material according to claim 1, characterized in that: The average particle size of the sand is 0.08-2.0 mm; the sodium silicate is liquid sodium silicate with a modulus of 28.

3. The alkali-activated gelling material according to claim 1, characterized in that: The invention is composed of the following raw materials in parts by weight: 170-190 parts of slag, 150-160 parts of garbage ash, 230-250 parts of fly ash, 110-130 parts of sodium silicate, 18-22 parts of NaOH, 145-155 parts of water and 1220-1240 parts of sand. The water-to-binder ratio of the alkali-activated cementitious material is 0.30-0.

36.

4. The alkali-activated gelling material according to claim 1, characterized in that: The invention is composed of the following raw materials in parts by weight: 180 parts of slag, 155 parts of garbage ash, 240 parts of fly ash, 125 parts of sodium silicate, 20 parts of NaOH, 150 parts of water, and 1220-1240 parts of the sand. The water-to-binder ratio of the alkali-activated cementitious material is 0.

34.

5. The alkali-activated gelling material according to claim 1, characterized in that: The slag density is 2.88 g / cm 3 , the density of garbage ash is 2.53g / cm 3 The density of fly ash is 1.81g / cm 3 .

6. A method for preparing the alkali-activated gelling material according to any one of claims 1 to 5, characterized in that: Use the following steps: (1) Dissolve NaOH in water to dissolve it; (2) uniformly mixing slag, garbage ash and fly ash to obtain a first mixture; (3) adding the NaOH solution prepared in step (1) into the first mixed material prepared in step (2), mixing them evenly, to obtain a second mixed material; (4) adding liquid sodium silicate into the second mixed material prepared in step (3), mixing them evenly, to obtain a third mixed material; (5) Adding sand into the third mixed material prepared in step (4), mixing them evenly, and obtaining the alkali-activated cementitious material.

7. Use of the alkali-activated gelling material according to any one of claims 1 to 5 and / or the alkali-activated gelling material prepared by the preparation method according to claim 6, characterized in that: Application of the alkali-activated cementitious material in bridge construction.

8. The use according to claim 7, characterized in that: The specific operation of the application is: pouring the prepared alkali-activated cementitious material onto the steel bridge deck, vibrating it to make it dense, smoothing the surface, and performing steam curing for 28 days.

Citation Information

Cited By

  • Environment-friendly high-performance cementing material based on fly ash and slag and preparation method thereof

    CN120208569A